Jamesdicksonia anadelphiae-trichaetae (Georgefischeriales) and Sporisorium anadelphiae-trichaetae (Ustilaginales), new species on Anadelphia trichaeta (Poaceae) from Guinea - Denchev, Teodor T.; Denchev, Cvetomir M. (Phytotaxa, 2016)
Two new smut fungi on Anadelphia trichaeta, namely Jamesdicksonia anadelphiae-trichaetae and Sporisorium anadelphiae-trichaetae, are described and illustrated from Guinea. Jamesdicksonia anadelphiae-trichaetae differs from J. anadelphiae, infecting Anadelphia pumila in Guinea, by having larger spores (up to 26.5 μm long), thicker spore walls (up to 9.0 μm thick), and erumpent sori. Sporisorium anadelphiae-trichaetae differs from S. monocymbii, infecting Monocymbium ceresiiforme in Sierra Leone, by having spore walls with more prominent ornamentation (spines up to 0.7 μm high) and larger spores. A key to the smut fungi on Anadelphia and related genera is provided.